Challenges faced by women entrepreneurs in rural India: The case of Avika. (February 2017) - Pathak, Atul Arun; Varshney, Sanjeev
Malavika Sharma, an Indian woman rural entrepreneur, founded Avika, a venture which produced traditional, hand-embroidered Indian garments. Avika grew rapidly and now provides employment to over 700 rural women. This case highlights various challenges that an entrepreneurial venture run by a woman, in a rural location within a traditional patriarchal society such as India, faces. The case also helps understand the inevitable inter-twining of business and social issues, given the rural context.